PEMANFAATAN MEDIA VIDEO PEMBELAJARAN UNTUK PENINGKATAN KEMAMPUAN SWAMEDIKASI OBAT PADA MAHASISWA D3 FARMASI - Fadli Fadli; Adhisty Kharisma Justicia; Billmar Carlos (Jurnal Farmasi IKIFA, 2021)
Self-medication is the effort that most people do to overcome complaints or symptoms of illness before they decide to seek help from a health service center. Students majoring in pharmacy as prospective pharmacists certainly have competency standards in the pharmaceutical field. One of these competency standards is drug self-medication skills, which of course will be very important to master when you graduate from pharmacy college. In the process, this can be achieved by using the most appropriate and effective learning media in accordance with the learning objectives. Sampling in this study used a purposive sampling technique with 30 respondents. This research method is a survey with a quantitative research type with data collection using a questionnaire. The conclusion of this study is that learning video media has an influence on increasing students' ability to self-medication by conducting a T test using the Paired Samples T Test method. From the data above, a significance value of 0.046 > 0.05 is obtained, it can be concluded that the hypothesis is accepted. Where the hypothesis of this research is that learning video media has an influence and can increase the ability of drug self-medication in D3 Pharmacy students.